Gender and Environmental Literacy on Islamic-based High School Students Under Spiritual Values - Muslih, Moh. (IAIN Pekalongan, 2021)
Environmental literacy may lead someone to act more responsibly towards the environment. This study aims to analyze gender differences in the environmental literacy of Islamic-based high school students. Although there have been many studies on similar topics, there is not much research found in the perspective of Islamic-based students, where they practice Islamic spiritual values about environmental sustainability. This study uses a quantitative approach using the multivariate analysis of variance (MANOVA) method to determine the effect of gender differences on students' environmental literacy levels. The sampling technique used is questionnaire distribution to as many as 53 students at a high school in Central Java who are randomly selected. Three dimensions of environmental literacy are analyzed; namely knowledge, attitudes, and pro-environmental behavior. The results of the analysis suggest that the students' literacy level is in a good category, which is at 80.67%. Islamic values that have been attached to students are believed to contribute to the level of environmental literacy of students. Then, the results also indicate those female students have better literacy levels in all dimensions. However, the results of the analysis found there is not enough evidence to suggest that male and female students differ significantly based on environmental literacy.